Model Perencanaan Sumber Daya Manusia di BKD Provinsi Jawa Timur: Sebuah Tantangan Menghadapi Pandemic Covid 19 - Mahmudin, M Nur Kharis; Hermawan, Hermawan; Hanafi, Imam (Jurnal Ilmiah Administrasi Publik, 2021)
Planning for employee needs at BKD East Java Province has an important role because it is related to getting the right employees, in the right number, with the right capabilities, at the right time, and in the right place to achieve organizational goals both in the short and long term. The problem is the unequal capacity of OPD employees in aligning the direction determined by the Central Government and there are advantages and disadvantages of employees in the organization. The purpose of this study was to identify and describe the planning model for employee needs in the BKD of East Java Province in dealing with the Covid-19 pandemic, both in terms of the process and the reasons. The results of the study show that the BKD of East Java Province innovated changes in the needs planning process by coordinating and aligning the network (online) to deal with the Covid-19 pandemic. This is done as a way to ensure that the planning carried out can provide accuracy for OPD in terms of quantity and quality. It is necessary to increase the internal capacity of the OPD in order to create a good planning for the needs of employees in the Regional Government.